Theoretical calculations for the superheated steam properties up to 8.0 MPa based on the ideal gas law with the compressibility factor Z - Sedong Kim; Sujeong Choe; Jae-Hyuk Choi; Soon-Ho Choi (Case Studies in Thermal Engineering)
Not only is superheated steam still widely used as a primary working fluid for driving various types of power generation systems, but it is also an essential intermediary substance for reforming fossil fuels. This study was conducted to extend the applicable range of the ideal gas law for calculating superheated steam properties by incorporating the compressibility factor. The compressibility factor was determined by evaluating the second Virial coefficient, and it was confirmed that this study is applicable up to the pressure of 8.0 MPa of superheated steam, which is a significant achievement. Additionally, the Redlich-Kwong equation was theoretically analyzed for the first time and its theoretical basis was established, which was not achieved even by the original authors. This thorough analysis of the Redlich-Kwong equation may serve as a new starting point for developing a new equation of state for gases and vapors.